Deceit on the Road to War : Presidents, Politics, and American Democracy - Schuessler, John M., 1977- (Book collections on Project MUSE., 2015)
In Deceit on the Road to War, John M. Schuessler examines how U.S. presidents have deceived the American public about fundamental decisions of war and peace. Deception has been deliberate, he suggests, as presidents have sought to shift blame for war onto others in some cases and oversell its benefits in others. Such deceit is a natural outgrowth of the democratic process, in Schuessler's view, because elected leaders have powerful incentives to maximize domestic support for war and retain considerable ability to manipulate domestic audiences. They can exploit information and propaganda advantages to frame issues in misleading ways, cherry-pick supporting evidence, suppress damaging revelations, and otherwise skew the public debate to their benefit. These tactics are particularly effective before the outbreak of war, when the information gap between leaders and the public is greatest. When resorting to deception, leaders take a calculated risk that the outcome of war will be favorable, expecting the public to adopt a forgiving attitude after victory is secured. The three cases featured in the book - Franklin Roosevelt and World War II, Lyndon Johnson and the Vietnam War, and George W. Bush and the Iraq War - test these claims. Schuessler concludes that democracies are not as constrained in their ability to go to war as we might believe and that deception cannot be ruled out in all cases as contrary to the national interst. -- from dust jacket.